A polymer lithium–oxygen battery based on semi-polymeric conducting ionomers as the polymer electrolyte. Issue 39 (20th September 2016) - Wu, Chaolumen; Liao, Chenbo; Li, Taoran; Shi, Yanqiong; Luo, Jiangshui; Li, Lei; Yang, Jun
Abstract : A polymer lithium–oxygen battery based on lithiated perfluorinated sulfonic conducting ionomers swollen with non-aqueous solvents operates at room temperature, showing good cycling stability, rate capability and a capacity as high as 1500 mA h gcarbon −1 . Abstract : A polymer lithium–oxygen battery based on lithiated perfluorinated sulfonic conducting ionomers swollen with non-aqueous solvents used as both the electrolyte and separator is successfully operated at room temperature, and shows good cycling stability and rate capability and is even operable for many cycles with a capacity as high as 1500 mA h gcarbon −1 . It demonstrates the suitability of the polymer lithium–oxygen battery as a high-energy storage system.